2015
DOI: 10.1155/2015/259627
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofSLC22A5Gene Mutation in a Family with Carnitine Uptake Defect

Abstract: Primary systemic carnitine deficiency is caused by homozygous or compound heterozygous mutation in the SLC22A5 gene on chromosome 5q31. The most common presentations are in infancy and early childhood with either metabolic decompensation or cardiac and myopathic manifestations. We report a case of 9-year-old boy with dysmorphic appearance and hypertrophic cardiomyopathy. Tandem MS spectrometry analysis was compatible with carnitine uptake defect (CUD). His sister had died due to sudden infant death at 19 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…As anticipated, given that these tissues are undergoing development, many of the 77 main cell types include states progressing from precursors to one or several terminally differentiated cell types. For example, cerebral excitatory neurons exhibited a continuous trajectory from PAX6+ neuronal progenitors to NEUROD6+ differentiating neurons (92) (96)(97)(98). In contrast with mouse organogenesis-wherein the maturation of the transcriptional program is tightly coupled to developmental time (11)-cell state trajectories were inconsistently correlated with estimated postconceptual ages in these data (fig.…”
Section: Identification and Annotation Of 77 Main Cell Typesmentioning
confidence: 78%
“…As anticipated, given that these tissues are undergoing development, many of the 77 main cell types include states progressing from precursors to one or several terminally differentiated cell types. For example, cerebral excitatory neurons exhibited a continuous trajectory from PAX6+ neuronal progenitors to NEUROD6+ differentiating neurons (92) (96)(97)(98). In contrast with mouse organogenesis-wherein the maturation of the transcriptional program is tightly coupled to developmental time (11)-cell state trajectories were inconsistently correlated with estimated postconceptual ages in these data (fig.…”
Section: Identification and Annotation Of 77 Main Cell Typesmentioning
confidence: 78%
“…It is known that the genetic variants related to IEMs are mainly detected by Sanger sequencing and MassARRAY ( Wright et al, 2008 ; Zhu et al, 2010 ; Shibbani et al, 2014 ; Mutlu-Albayrak et al, 2015 ). Recently, next generation sequencing (NGS) started to be applied for the clinical genetic analysis of IEMs ( Qian et al, 2017 ; Smon et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our molecular analysis showed that the patient carries a heterozygous missense variant, c.1345T>G (p.Y449D, p.Tyr449Asp), in the SLC22A5 gene located in exon 8, and expression studies of variants showed that Y449D has a functional effect [5,20]. PCD is caused by both homozygous or compound heterozygous mutations in SLC22A5 on chromosome 5q31, and new cases of heterozygous mutations have recently been described [21,22]. ASD has only been reported in cases of PCD in this study, and in one previous case report of a child with developmental delay [23]; therefore, ASD does not appear to occur with an increased frequency among patients with PCD.…”
Section: Discussionmentioning
confidence: 99%